Abdominal Wall Endometriosis: Analysis of 66 Patients at a Tertiary Center - Besim Haluk Bacanakgil; Hasene Özçam; Mustafa Deveci; Sezgi Güllü Yıldırım (İstanbul Medical Journal, 2019)

(untitled)
Introduction:The objective of this study was to review the patients’ characteristics and surgical findings of surgically excised abdominal wall endometriosis (AWE) cases.Methods:We retrospectively analyzed the medical records of patients diagnosed with AWE between 2005 and 2015. Descriptive data were collected and analyzed.Results:Sixty-six patients with histopathological diagnosis of AWE were included in our study. The mean age was 32±6.8 years and all cases were multiparous. All patients had a history of previous abdominal surgery and 63 patients had a history of cesarean delivery. The primary symptom was a painful palpable mass. The excised mass was generally on the previous surgical scar. The excised mass location was observed as subcutaneous tissue, fat layer, fascia and muscle tissue. There was no statistical correlation depth of invasion and mass size with the number of previous surgeries.Conclusion:Caesarean incision was considered as the most important predisposing factor for AWE. As caesarean rates are increasing, we believe that the incidence of AWE will increase in the future. For this reason, more prospective studies are needed for prognosis and prophylaxis of the disease.